Space-time dynamics of planted forests in the Grão-Mogol microregion - Veloso, Gabriel Alves (2013)
The present study aims to analyze the temporal dynamics of planted forests in the microregion of Grão Mogol, and in their communities in the years 1986, 1996 and 2010. This microregion is located in the north of Minas Gerais between the geographical coordinates 43 34’32 “and 42 23’08” west longitude and 17 14’37 “and 16 07’03” south latitude in the analysis the micro data of microregion appears with a higher percentage of occupancy of planted forests, as they relate to their area of the same, with the years 1986, 1996 and 2010 planted area of 12.28%, 13.00% and 7% respectively. In relation to municipalities, Grão Mogol appears with the largest area of planted forests in the periods analyzed, since the municipality of Padre Carvalhopresents the highest percentage of occupation as it relates to your area.